Effects of time delay and tension system application after final flask closure on the vertical displacement of acrylic and porcelain teeth in maxillary complete dentures - Hussein, Ali N (Journal of Baghdad College of Dentistry, 2013)
Background: The displacement of artificial teeth during complete denture construction presents major processing errors in the occlusal vertical dimension which were verified at the previous trial denture stage. The aim of this study was to assess the effect of delay in processing after final flask closure and tension application on the vertical acrylic and porcelain teeth displacement of complete dentures constructed from heat cured acrylic and the results were compared with the conventional processing method. Materials and methods: forty samples of identical maxillary complete dentures were constructed from heat polymerized acrylic resin. These samples were subdivided into the following experimental subgroups in which each subgroup contains 5 samples for both acrylic and porcelain teeth and as follows: 1. Conventional flasking technique and immediate processing. 2. Conventional flasking technique and 6 hours delay in processing. 3. flasking technique with tension system and immediate processing. 4. flasking technique with tension system and 6 hours delay in processing. Reference metal pins were attached to the middle of the buccal surface of the upper right canine and center of the buccal groove of the left first molar. And according to these reference points on the teeth another metallic Reference pins were fixed on the denture vestibules and at a distance of 7.5mm by straight lines and 6.5mm where placed between the metal pins and the vestibules in order to standardize the measurement. The distance between the right and left metal pins on the canine and molars and the corresponding metal pins on the buccal vestibules were measured during the wax up stage and after processing by using an optical travelling microscope with an accuracy of 0.0005 mm. Means in (mm) were analyzed statistically by analysis of variance and the comparative T-test and least significance test (LSD). Results: Significant reduction in vertical displacement of the teeth occurred in groups when 6 hours delay in processing were applied, but a significant improvement was also observed in groups with tension system application when compared with control group. On the other hand, there were a high significant reduction in the vertical displacement in groups with tension system and 6 hours delay in processing combination. While for the type of artificial teeth data showed significant difference in the amount of vertical displacement of the teeth in groups with acrylic teeth when compared with porcelain teeth. Conclusions: The findings of this study showed that 6 hours delay in processing and tension system application were effective in reducing the vertical displacement of the artificial teeth during flasking. The maximum reduction in the displacement was observed in dentures constructed from acrylic teeth. On the other hand, significant decrease in vertical displacement of the teeth was detected in dentures constructed from porcelain teeth.